BEDMAP1 - Ice thickness, bed and surface elevation for Antarctica - gridding products ... - Lythe, Matt; Vaughan, David; BEDMAP 1 Consortia (NERC EDS UK Polar Data Centre, 2023)
We present here BEDMAP1 (2000-2001), a suite of gridded products describing surface elevation, ice-thickness and the sea floor and subglacial bed elevation of the Antarctic south of 60deg S. The suite includes grids representing: - ice-sheet thickness over the ice sheet and shelves, - bed elevation beneath the grounded ice sheet, - bathymetry to 60 degrees South including the areas beneath the ice shelves. These grids are consistent with a high-resolution surface elevation model of Antarctica. While the digital models have a nominal spatial resolution of 5 km, such high resolution is not strictly justified by the original data density over all parts of the ice sheet. The suite does however provide an unparalleled vision of the geosphere beneath the ice sheet and a more reliable basis for ice sheet modelling. The bed elevation DEM, which includes the entire geosphere south of 60 degrees South, provides an improved delineation of the boundary between East and West Antarctica and sheds new light on the ... : The primary source data consist of survey point measurements of ice thickness, bed elevation and surface elevation, which principally comes from airborne radar surveys and seismic soundings, and to a smaller extent from ground-based radar surveys. ...